A randomised controlled trial of a self-management programme for low vision implemented in low vision rehabilitation services. Issue 2 (February 2015) - Rees, Gwyneth; Xie, Jing; Chiang, Peggy P.; Larizza, Melanie F.; Marella, Manjula; Hassell, Jennifer B.; Keeffe, Jill E.; Lamoureux, Ecosse L.
Highlights A trial of a low vision self-management programme (LVSMP) in low vision services. Participants randomly allocated to usual services or usual services plus LVSMP. No significant group differences were found for vision-specific quality of life. A generic LVSM programme may not adequately meet the needs of a diverse group. Implications for delivery of LVSMP in practice need to be addressed.